Strategies for Developing Teacher Professional Competence in the Era of Digital Transformation in Education: A Literature Review - Marnoko Marnoko (Lembaga Riset Mutiara Akbar, 2025)
he digital transformation of education requires teachers to possess adaptive professional competencies aligned with technological advancements and 21st-century learning dynamics. This study aims to analyze strategies for developing teacher professional competence in the digital era through a systematic literature review of 23 national and international journal articles published between 2015 and 2025. The analysis employed a thematic approach based on the PRISMA model, encompassing stages of identification, selection, data extraction, and synthesis. The findings reveal that effective teacher professional development (TPD) strategies include continuous digital training, collaborative learning communities, and the integration of technologies such as artificial intelligence (AI) in training processes. Major challenges involve digital inequality, infrastructural limitations, and resistance to change. Overall, digital transformation positively impacts teachers’ pedagogical competence, technological literacy, and professional identity. This review recommends a sustainable, collaborative, and innovation-based TPD model to strengthen teachers’ roles as agents of educational transformation in the digital age.